The Relevance of the Concept of Ta'zir in the Contemporary Islamic Criminal Law System: A Study of Islamic Criminal Law and Its Application - WanNaila Safira; Iqbal Fahlevi; M. Hairil Suhdi Siregar; Rizki Maulidia Isnin Lubis; Muhammad Arsya (ISNU Sumatera Utara, 2025)
The concept of ta'zir is an important element in Islamic jurisprudence (fiqh jinayah), which serves as an instrument of Islamic criminal law outside the provisions of hudud and qisas. Unlike hudud, which are rigid, ta'zir offers flexibility in determining the type and level of sanctions, which are determined by judges based on considerations of justice and public interest. This study aims to examine the relevance and potential application of ta'zir in addressing the complexity of criminal acts in the contemporary era. The method used is qualitative research through library research, analyzing various classical and modern literary sources. The results show that the development of modern crimes, such as cybercrime, corruption, and human trafficking, requires a responsive legal mechanism. In this context, ta'zir functions as an adaptive instrument that can address these challenges, by providing room for judges to impose sanctions appropriate to the characteristics of the crime and the perpetrator's condition. In several Muslim countries, such as Brunei Darussalam, Malaysia, and Aceh, Indonesia, ta'zir has been integrated into the positive legal system. However, the implementation of ta'zir also requires strict regulations to avoid violating the principles of justice and human rights. Therefore, strengthening regulations and supervision in the implementation of ta'zir is important to ensure its effectiveness and relevance in the contemporary Islamic criminal law system.